Pengaruh Perputaran Kas dan Perputaran Piutang terhadap Profitabilitas PT Ultra Jaya Milk Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2012-2021 - Gunawan, Andri; Sarjana, Samuel Horas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This study aims to determine the effect of cash turnover and accounts receivable turnover on profitability (ROA) at PT. Ultra Jaya Milk Tbk for the 2012 -2021 period in quarterly terms. The method used in this research is quantitative. This study uses secondary data in the form of financial reports of PT. Ultra Jaya Milk which is listed on the Indonesia Stock Exchange and sampling was carried out using the non-probability sampling method, namely the saturated sample. Data analysis techniques use descriptive data and correlation with a significant level of 5%. Based on the results of the partial study, cash turnover has a negative effect with a t-count value of -2.734 <t-table 2.026 and is significant for profitability with a value of 0.010 <0.05, while receivables turnover has a positive effect with a t-count value of 10.271> t table 2.026 and is significant for profitability. With a value of 0.000 <0.05. Meanwhile, simultaneously cash turnover and accounts receivable turnover show that F count is 69,438 > F table 3.25 with a significance level of 0.000 < a significance level of 0.05 so that it can be concluded that it has a positive and significant effect. The R square value of 0.794 which shows 79.4% ROA can be explained by independent variables, while the remaining 20.6 is explained outside of other variables.